Tres traduccions angleses del capítol 436 del «Tirant lo Blanch» - Wittlin, Curt (Caplletra. Revista Internacional de Filologia, 1997)
This paper analyses the history of three English translations of Tirant lo Blanch which are currently available. In order to show the working method of each translator, Wittlln compares the three English versions of one of the most famous chapters of the novel, which is that of the love affair between Tirant and Carmesina in La Fontaine’s, Rosenthal’s and Rudder’s version. The translations of Tirant lo Blanch confirm the translators’ great power and the importance of their way of understanding literary works when reproducing the original aesthetic canons.